Study on the Effects of Kuanxiong Aerosol on the Isolated Artery and Rabbits Acute Myocardial Ischemia Model - Liu, Xia; Huang, Feihua; Lu, Xiao; Wang, Yuji; Cai, Tingting; Peng, Aiping; Zhu, Wanping (Combinatorial Chemistry & High Throughput Screening, 2022)
Background: Kuan Xiong aerosol (KXA) is a Chinese herbal compound used to regulate qi-flowing to relieve pain and improve angina. However, only a few pharmacological studies on this traditional Chinese medicine preparation have been reported to confirm these activities. Objectives: This article aims to observe the effect of resisting acute myocardial ischemia (AMI) in vivo and dilating vessel in vitro of KXA. Methods: The AMI model involves intravenously injecting the pituitary (2 U.kg-1) into the ear of rabbits. Electrocardiograph (ECG) T waves were then recorded after administration, and the falling range was calculated. Following this, the level of serum Cardiac troponin T (cTn-T) and the histopathology of the cardiac muscle tissue were evaluated. In vitro, the effect of KXA on vasodilation of isolated aortic rings that had been pre-contracted with KCl (30 mM) was observed. Results: It was found that KXA reduced ECG ST-T waves and serum cTn-T in the rabbit AMI model, protecting myocardial tissue from fracturing and loss of myocardial fibers and inhibiting inflammatory cell infiltration, cavitation degeneration, and karyopyknosis of the myocardial matrix. Furthermore, the administration of 0.215, 1.075, and 2.150 mg.mL-1 of KXA resulted in significant relaxation of the aortic rings at a rate of 69.63 %, 90.14 %, and 118.72 % (p < 0.01) in the untreated ones, and a second shrinkage ratio of 20.17 %, 4.29 %, and 4.54 % (p < 0.01) in the untreated ones, respectively. Conclusion: These results suggest that KXA protects against AMI, contributes to the dilation of blood vessels, and has long-acting effectiveness.
Keywords: acute myocardial ischemia